1986
DOI: 10.1113/jphysiol.1986.sp016014
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics of histamine secretion from rat peritoneal mast cells stimulated with nerve growth factor.

Abstract: SUMMARY1. Nerve growth factor (NGF) isolated from mouse submandibular gland or from snake venom produced a dose-dependent release of histamine from isolated rat peritoneal mast cells.2. The response was almost totally dependent on the presence of extracellular calcium ions and on added phosphatidylserine or its lyso-derivative.3. At high concentrations, strontium ions could substitute for calcium. 4. The process was non-cytotoxic, relatively slow, pH dependent and blocked by polyclonal antibodies to NGF.5. Bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(101 citation statements)
references
References 28 publications
(47 reference statements)
8
92
1
Order By: Relevance
“…In addition to the immunological stimulation, intradermal or s.c. administration of NGF to rats causes immediate vasodilatory responses characterized by the degranulation of local mast cells (23,24). In contrast with the in vivo reports, NGF alone is insufficient to induce chemical mediator release from rat peritoneal mast cells (PMC) and the addition of exogenous phosphatidylserine (PS) or lysoPS, a deacylated PS derivative, to NGF is necessary for the mast cell activation (8,25,26). However, the mechanisms by which NGF and serinephospholipids induce mast cell activation and their pathophysiological roles have been poorly understood.…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 74%
See 2 more Smart Citations
“…In addition to the immunological stimulation, intradermal or s.c. administration of NGF to rats causes immediate vasodilatory responses characterized by the degranulation of local mast cells (23,24). In contrast with the in vivo reports, NGF alone is insufficient to induce chemical mediator release from rat peritoneal mast cells (PMC) and the addition of exogenous phosphatidylserine (PS) or lysoPS, a deacylated PS derivative, to NGF is necessary for the mast cell activation (8,25,26). However, the mechanisms by which NGF and serinephospholipids induce mast cell activation and their pathophysiological roles have been poorly understood.…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 74%
“…In this study, we clearly demonstrated that NGF led to mediator release from mast cells through the collaborative interaction with activated platelets in vitro. This effect was not substantially influenced by a fixation of activated platelets with paraformaldehyde, suggesting that certain membrane molecules, such as PS or lysoPS (8,25,26) expressed on the platelet surface after stimulation with calcium ionophore or thrombin may be involved in NGF-mediated mast cell activation. Because NGF-induced 5-HT release was detected in the presence of lysoPS or lysoPS-expressing RBC, but not PS or PS-expressing RBC, lysoPS rather than PS may act as an alternative potential molecule for NGF-induced mast cell activation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…26 NGF recruits mast cells and promotes their degranulation. 36,37 Both of these are early events in a developing lesion of psoriasis. In addition, NGF activates T lymphocytes, recruits inflammatory cellular infiltrates, [37][38][39][40] is mitogenic to endothelial cells, and induces ICAM on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the hyperalgesia generated by the inflammation resulting from complete Freund's adjuvant (CFA) injection, is significantly reduced by systemic administration of a specific anti-NGF antiserum , implying that NGF contributes directly or indirectly to inflammatory sensitivity changes. The indirect effects of NGF may result from its cytokine-like actions, including stimulation of growth and differentiation of human B lymphocytes Thorpe et al, 1988;Treede et al, 1992), the release of inflammatory mediators from lymphocytes and basophils (Bischoff & Dahinden, 1992;Horigome et al, 1993) and a degranulation of mast cells (Aloe & Levi-Montalcini, 1977;Bohm et al, 1986;Mazurek et al, 1986;Pearce & Thompson, 1986). Direct effects could either be due to a trkA receptor-tyrosine kinase-mediated phosphorylation at the nociceptor terminal, increasing transduction sensitivity, or a consequence of a change in the expression of transmitter/neuromodulators such as substance P and calcitonin gene-related peptide (CGRP) in the cell body (Lindsay & Harmar, 1989;Woolf et al, 1994), amplifying the central actions of the nociceptor in the spinal cord (Lewin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%